Perilipin 2 inhibits replication of hepatitis B virus deoxyribonucleic acid by regulating autophagy under high-fat conditions - Delpino, María Victoria (2024)
Hepatitis B virus (HBV) infection poses a global health concern without adefinitive cure; however, antiviral medications can effectively suppress viralreplication. This study delves into the intricate interplay between lipid metabolism and HBV replication, implicating molecular mechanisms such as the stearoylcoenzyme A desaturase 1 autophagy pathway, SAC1-like phosphatidylinositolphosphatase, and galectin-9 mediated selective autophagy of viral core proteins inregulating HBV replication. Within lipid droplets, perilipin 2 (PLIN2) emerges asa pivotal guardian, with its overexpression protecting against autophagy anddownregulation stimulating triglyceride catabolism through the autophagypathway. This editorial discusses the correlation between hepatic steatosis andHBV replication, emphasizing the role of PLIN2 in this process. The studyunderscores the multifaceted roles of lipid metabolism, autophagy, and perilipinsin HBV replication, shedding light on potential therapeutic avenues.